1996
DOI: 10.1111/j.1469-8986.1996.tb02120.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of blood pressure and heart rate reactivity: A meta‐analysis

Abstract: Reproducibilities of blood pressure and heart rate (HR) reactivity reported in studies assessing responses to the same laboratory stressors across occasions were reviewed with meta-analytic techniques. Changes in HR had the greatest reproducibility (r = .555), followed by systolic blood pressure (SBP) (.407) and diastolic blood pressure (DBP) (.348). Both SBP and HR response reproducibility was higher at shorter test-retest intervals, whereas DBP values varied unsystematically with length of test-retest interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
46
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 91 publications
5
46
1
Order By: Relevance
“…About the cardiovascular parameters, the three most commonly used in these studies were HR, SBP and DBP (Swain & Suls, 1996), to combine the criteria and to enhance the comparison between different results from various research studies. All the parameters have been captured, recorded, stored and analyzed in a highly reliable, non invasive and continuous manner, which is especially relevant in the case of blood pressure.…”
Section: Resultsmentioning
confidence: 99%
“…About the cardiovascular parameters, the three most commonly used in these studies were HR, SBP and DBP (Swain & Suls, 1996), to combine the criteria and to enhance the comparison between different results from various research studies. All the parameters have been captured, recorded, stored and analyzed in a highly reliable, non invasive and continuous manner, which is especially relevant in the case of blood pressure.…”
Section: Resultsmentioning
confidence: 99%
“…One may speculate whether test-retest reproducibility of stress reactivity is sufficient enough to give the present findings prognostic value. Because stability has been found to increase when the number of measurements during stress tests increase, 41 we performed 3 measurements during mental arithmetic and 2 during the cold pressor test and then calculated the mean during each test. There are, however, as yet no data available on the reproducibility on catecholamine reactivity.…”
Section: Flaa Et Al Sympathoadrenal Activity Predicts Blood Pressurementioning
confidence: 99%
“…Psychometric studies have established satisfactory temporal stability of the commonly used cardiovascular reactivity measures, particularly when aggregated over multiple stressors (18,19). Prospective studies have shown that these individual differences in cardiovascular reactivity predict future hypertension (20 -22) and atherosclerosis (23,24).…”
Section: Introductionmentioning
confidence: 99%